Impact of Trend Analysis On Quality Of Finished Products In A Pharmaceutical Industry - Orukotan, A. A.; Oloninefa, S. D. (UMYU Journal of Microbiology Research)
In this study, trend analyses were carried out on the results obtained for microbiology purity tests and assay of 25 batches of Paracetamol Syrup obtained from a selected Pharmaceutical Industry within Minna Metropolis using the 3-Sigma Method. The results of the trend analyses showed the trend ranges of 60±31; 13.6±31 and 102.31±31 for Total Viable Aerobic Mesophilic Bacteria Plate Count, fungi and the assay respectively. The study showed that the results obtained from the trend analyses carried on all the results obtained for microbiology purity tests and assay of 25 batches of Paracetamol Syrup were within the trend ranges calculated and this suggest that the quality of the 25 batches of Paracetamol Syrup analysed were of good quality microbiologically and chemically.